Challenges faced in bringing a comprehensive digital transformation in customer relationships and internal processes in Indian retail companies and their successful implementation - Bagga, Simran (2016)
This study aims at investigating the challenges faced by traditional medium scale Indian retail businesses while they are making their way to digital transformation of their businesses and give recommendations for successful implementation of digitization by overcoming these challenges. Qualitative research was conducted which involved taking interviews from retail business owners in India. The interviews involved asking their views on digital scope in their sector, practical challenges they face during new technology use and why do they have a level of resistance towards ‘digital.